The capacity of emotions in the work environment - Reyes Abundes, Mariana (2021)
The objective of this article is to investigate by means of the content analysis method 1) texts that deal with the theory of emotions, as well as 2) articles that study emotions applied to the work environment, in order to show the state of the art on this subject, identifying the ways in which these bonds are constructed. To this end, the first part deals with the components of emotions, and the second part analyzes the relationship between emotions and the work environment. It is intended to show the discourse on how they influence ethical decision making from an organizational perspective. Finally, strategies to educate employees and organizations towards the development of emotions are proposed, and a table derived from the content analysis is provided.